Phytochemical Compositions, Nutritional Contents, Cytotoxicity and Anti-Inflammatory Activity of Different Extracts from Spirogyra neglecta (Hassall) Kützing - Yongkhamcha, Butsara; Buddhakala, Nopparat (Trends in Sciences, 2023)
Spirogyra neglecta (Hassall) Kützing is an edible freshwater macroalga. It is available and consumed as local food in Thailand, especially in the northern and northeastern parts. To ascertain its good benefit for health and safe for consumption, this study was, therefore carried out to determine the phytochemical compositions, nutritional contents, cytotoxicity, and anti-inflammatory activity of the different extracts from S. neglecta. The extracts were prepared by using different solvents, such as propylene glycol, methanol, and ethanol solutions. GC-MS analysis revealed the presence of 30, 39 and 36 phytochemical compounds in propylene glycol, methanol, and ethanol extracts, respectively. Phytol, which has been reported to have anti-inflammatory activity, was one of the predominant compositions in the extracts. The extracts contained high nutritional contents of protein, lipid, fiber, ash, moisture, and carbohydrate up to 21.68 ± 4.52, 3.53 ± 0.23, 14.77 ± 0.89, 10.73 ± 0.47, 9.79 ± 0.11 and 47.36 ± 3.89 %, respectively. The highest total protein was found in propylene glycol extract. The highest total lipid was in ethanol extract. Meanwhile, the highest fiber, ash and total carbohydrate were in methanol extract. In addition, all the extracts possess relatively low cytotoxicity, with IC50 values greater than 1,000 µg/mL. The extracts 1,000 µg/mL exhibited anti-inflammatory activity via inhibition Nitric oxide (NO) production by 29.87 ± 1.56 to 55.17 ± 1.91 %. The propylene glycol extracts from S. neglecta showed the highest inhibitory activity on NO production compared to others. The overall results indicating the propylene glycol is the solvent that produces the best extraction performance. The extracts from S. neglecta exhibit anti-inflammatory activity by inhibiting NO production. The phytochemical compositions are partly responsible for anti-inflammatory activity of the extracts. The high nutritional contents complement relatively low toxic. Thus, S. neglecta can be used as benefit natural sources for food products, supplements, and medicinal plants. HIGHLIGHTS Using GC-MS analysis, there are 30, 39 and 36 phytochemical compounds in propylene glycol, methanol and ethanol extracts from Spirogyra neglecta, respectively The extracts from neglecta possess high nutritional contents of protein, lipid, fiber, ash, moisture, and carbohydrate The extracts from neglecta show relatively low toxic to the RAW 246.7 cells with LC50 >1,000 µg/mL, by MTT assay The extracts from neglecta exhibit anti-inflammatory activity by inhibition of NO production. The propylene glycol extract displays the highest activity compared to others The anti-inflammatory activity of the extracts is partially from Phytol GRAPHICAL ABSTRACT